Anode Materials: Realizing Reversible Conversion‐Alloying of Sb(V) in Polyantimonic Acid for Fast and Durable Lithium‐ and Potassium‐Ion Storage (Adv. Energy Mater. 1/2020). Issue 1 (7th January 2020) - Wang, Boya; Deng, Zhiwen; Xia, Yuting; Hu, Jiaxuan; Li, Hongju; Wu, Hao; Zhang, Qiaobao; Zhang, Yun; Liu, Huakun; Dou, Shixue
Abstract : In article number 1903119, Hao Wu, Yun Zhang, and co‐workers report the synthesis and use of 3D tunnel pyrochlore structured polyantimonic acid nanooctahedra with internal voids, which work together with N‐doped graphene nanosheets, as the anode materials for both lithium‐ and potassium‐ion batteries. The constructed composite enables fast ionic diffusion, increased electrical conductivity, and inside‐out volume expansion buffer for successfully realizing reversible conversion‐alloying of Sb(V) toward Li + /K + storage.